Movement related potentials and oscillatory activities in the human internal globus pallidus during voluntary movements. Issue 1 (23rd June 2011) - Tsang, Eric W; Hamani, Clement; Moro, Elena; Mazzella, Filomena; Lozano, Andres M; Hodaie, Mojgan; Yeh, I-Jin; Chen, Robert
Abstract : Objective: To study internal globus pallidus (GPi) activities and the interactions among the bilateral GPi and motor cortical areas during voluntary movements. Methods: Five patients with cervical dystonia who underwent bilateral GPi deep brain stimulation (DBS) were studied. Local field potentials from the GPi DBS electrodes and EEG were recorded while the patients performed externally triggered and self-initiated right wrist movements. Results: Movement related potentials were recorded at the GPi bilaterally before the onset of self-initiated but not externally triggered movements. In all movements studied, frequency analysis revealed a ∼10–24 Hz beta event related desynchronisation at bilateral GPi and with EEG recorded over the mid-frontal (Cz-Fz) and the bilateral sensorimotor cortical regions (C3/C4-Cz). A ∼64–68 Hz, gamma event related synchronisation was found with EEG recorded over the mid-frontal (Cz-Fz), the sensorimotor cortices (C3-Cz) and the GPi contralateral to movements. Both beta event related desynchronisation and gamma event related synchronisation occurred before the onset of self-initiated movements and at the onset of externally triggered movements. There was a resting ∼5–18 Hz coherence between the bilateral GPi, which attenuated for ∼1 s during movements. Gamma coherences were observed between EEG recorded over the mid-frontal (Cz-Fz), contralateral sensorimotor cortices (C3-Cz) and the GPi from 0 to 0.5 s after movement onset for externally triggered movements and from 0.5 s before to 0.5 s after movement onset for self-initiated movements. Conclusions: The beta and gamma frequency bands in the GPi are modulated by the preparation of self-initiated movements and the execution of self-initiated and externally triggered movements. The 5–18 Hz coherence at the bilateral GPi may be related to dystonia and its attenuation may facilitate voluntary movements.